Effect of Different NaOH Solution Concentrations on Mechanical Properties and Microstructure of Alkali-Activated Blast Furnace Ferronickel Slag - Zongxian Huang (MDPI AG, 2021)
Blast furnace ferronickel slag (BFFS) is a kind of industrial solid waste that has not been effectively utilized in construction industry. The effects of different NaOH concentrations on the mechanical properties and microstructure of alkali-activated blast furnace ferronickel slag were investigated in this study. The results show that an optimal concentration for compressive strength is found, both higher and lower concentrations cause strength degradation. The pore structure, phase composition and hydration heat revealed that less C-A-S-H gel is produced at low concentration and result in the low compressive strength The phase composition and hydration heat revealed that more hydrotalcite is produced than C-A-S-H at high concentration due to more violent reaction at the early age hinders the growth of C-A-S-H in the later stage. FT-IR also shows that high concentration decreased the Al/Si ratio and polymerization of C-A-S-H which also leads to the low strength at high concentration.